Optimization of subcritical water-mediated lipid extraction from activated sludge for biodiesel production. Issue 8 (14th September 2021) - Edeh, Ifeanyichukwu; Overton, Tim; Bowra, Steve
Abstract: The search for a cheap and readily available feedstock for biodiesel production has driven researchers to investigate the potential use of activated sludge-derived lipid. Due to the low lipid yield of activated sludge, the utility of subcritical water (SCW) is being considered as a means of increasing the extractable lipids. In this work, operating parameters (temperature, time and biomass loading) identified in our previous work to influence lipid yield from activated sludge under SCW treatment were optimized, using face-centered central composite design (FCCCD). The results show that the maximum lipid yield obtained from the liquid and solid products, post SCW treatment, at the optimum conditions of temperature 80 °C, extraction time 20 min and biomass loading 1%, was 41.0 (wt./wt.)%. This gives approximately 454 (wt./wt.)% increase from 7.4 (wt./wt.)% obtained by solvent extraction without SCW treatment. The results suggest that activated sludge is a potential feedstock for biodiesel production.